The differences between students with high and low academic performance - Siti Khadijah, Nayan (2017)
The main aim of this study was to analyze the between students with high and low academic performance in term of parent social economic status, physical activity and motivation. This study was conducted in University Utara Malaysia with UUM College of Arts and Sciences, UUM College of Business, and UUM College of Law, Government and International Studies, Kedah, Malaysia. The sample of this study consists of 261 respondents from the UUM postgraduate students which consist of Phd and Master Students. Data were collected through questionnaires paper survey. The data were analyzed using various statistical techniques such as reliability analysis, descriptive analysis and Chi Square Test to analyses the differences students with higher and lower academic performance in term of parent social economic status, physical activity and motivation. The analyses were carried out via Statistical Package for Social Science (SPSS) version 23.0 version for Windows. Based on the descriptive analysis, independent variable (motivation) have significant relationship toward academic performance and for Chi Square Test results, there was clear indication that the independent variable (parent educational level, mother occupation) have significant association or relationship toward academic performance. On the other hand, independent variable (parent income level, father occupation, physical activity) have no significant toward academic performance.